Respecting the balance of political information at Congolese National Radio and Television - LIFOLI BALEA, Jean-Pierre; Balea, Lifoli; Sashi, Christian Uzilo; MokiangoYinda, Trésor (IJRDO - Journal of Applied Management Science, 2018)
This article is the result of the observation made on the manner to collect, to treat and to distribute the information that come from surroundings politics by the RTNC, the main public media in DRC.  After four months of observation, we noted that the RTNC reserves 99% of time in place on the news of the power against 0,6% to the opposition.  This unbalance demonstrates that the RTNC, supposed to be to the service of all political currents of the country takes position in place in favor of the party to the power in Democratic Republic of Congo. Consequently, the broadcasts of the RTNC are despised and less consistent by the majority of the Congolese populations and especially the intellectuals.